What potential risk reduction could be achieved with evolocumab treatment? A simulation based on observational data from a cohort of users in 10 European countries. (25th November 2020) - Ray, K.K; Bridges, I; Bruckert, E; Van Hout, B; Sibartie, M; Villa, G
Abstract: Background/Introduction: The FOURIER trial enrolled very high-risk patients with a mean LDL-C of 2.5 mmol/L, and demonstrated that evolocumab reduced major cardiovascular events by 1.5% in absolute terms over 2.2 years. Further research may be conducted to understand the potential benefits of evolocumab in the real world. Purpose: Predict/simulate baseline CV risk and assess potential risk reduction among a large European cohort of evolocumab users. Methods: We used interim data from an observational study of patients initiating evolocumab across 10 European countries from August 2015 with follow-up through October 2019. Demographic and clinical characteristics, lipid-lowering therapy (LLT) and lipid values were collected from routine medical records (6 months prior to evolocumab initiation through 30 months post initiation). For each patient, we 1) predicted/simulated their 10-year CV risk using three different approaches: i) a prediction using REACH score, ii) a simulation based on FOURIER trial patients, iii) a simulation based on real-world FOURIER-like patients from a published obervational study; 2) calculated their absolute LDL-C reduction on evolocumab treatment; 3) simulated their relative risk reduction (RRR) by randomly sampling from the probability distribution of the rate ratio per 1 mmol/L from the key secondary endpoint in the FOURIER trial landmark analysis; 4) calculated their absolute risk reduction (ARR). Results: Our analysis included 779 patients initiating evolocumab in clinical practice per local reimbursement criteria, with up to 18 months follow-up. Mean (SD) age was 62.7 (9.6) years and mean (SD) baseline LDL-C was 3.85 (1.39) mmol/L. Mean (SD) absolute LDL-C reduction on evolocumab was 2.1 (1.2) mmol/L. Predicted/simulated 10-year CV risk, RRR and ARR are presented in Table 1. Simulated probability distributions (based on FOURIER) for 10-year CV risk before and after evolocumab treatment are shown in Figure 1. Conclusion(s): This cohort of evolocumab users in clinical practice had an almost 2-fold higher baseline LDL-C than patients enrolled in FOURIER trial, which translated to higher baseline CV risk. For that reason, the estimated 10-year absolute benefit in this cohort was larger than expected based on FOURIER trial results. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Amgen